Optimization of the Industrial use of Renewable Energy for Sustainable and Cost Effective Rural Electrification - Njoku, C. O.; Gambo, A. V.; Uche, E. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
There is an inequitable access of rural communities to electricity services in Nigeria as demand supersedes generation. The provision of viable electricity to rural communities is hampered by some inefficiency bedeviling the allocation of energy resources coupled with the near depletion of fossil fuels. Due to capital intensive nature of renewable energy sources; most of these energy sources remain unexploited in Nigeria. This study aims at developing a general framework that can be utilized in Nigeria to minimize the total cost of installing renewable energy technologies while satisfying some predetermined constraints such as demand, supply and renewable energy potentials. Three scenarios were presented namely; prospective off-grid which accesses electricity level below 50%, on-grid which accesses electricity level above 50% and all-off-grid which finds the optimal cost of installing off-grid renewable energies. The results show that the total installation costs of the first and second scenarios are ₦42,656,292,800 and ₦49,908,650,400 respectively while that of the third scenario is found to be ₦106,938,354,400 which represent the extent of renewable energy resources that could possibly incentivize the realization of wider renewable energy applications in rural Nigeria. Furthermore, it was observed that the combination of the off-grid and on-grid installations have the potential for a decentralized renewable energy resources, with minimum installation cost. This will not only improve the wellbeing of rural communities, but also enhance Nigeria’s energy and economic prospects for potential global investments.